2012
DOI: 10.3897/zookeys.215.1731
|View full text |Cite
|
Sign up to set email alerts
|

Aphanius arakensis, a new species of tooth-carp (Actinopterygii, Cyprinodontidae) from the endorheic Namak Lake basin in Iran

Abstract: A new species of tooth-carp, Aphanius arakensis sp. n., is described from the Namak Lake basin in Iran. The new species is distinguished by the congeners distributed in Iran by the following combination of characters: 10–12 anal fin rays, 28–32 lateral line scales, 10–13 caudal peduncle scales, 8–10 gill rakers, 12–19, commonly 15–16, clearly defined flank bars in males, a more prominent pigmentation along the flank added by relatively big blotches in the middle and posterior flank segments in females, a short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 29 publications
5
53
0
Order By: Relevance
“…In this group, A. hormuzensis from Hormuzgan is clustered with A. stoliczkanus from the Mond basin. This is in agreement with the results of Teimori et al (2012a) where they analysed fish body and otolith morphology and found a close relationship between these two species (Teimori et al, 2012a;page 301, Fig. 6).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this group, A. hormuzensis from Hormuzgan is clustered with A. stoliczkanus from the Mond basin. This is in agreement with the results of Teimori et al (2012a) where they analysed fish body and otolith morphology and found a close relationship between these two species (Teimori et al, 2012a;page 301, Fig. 6).…”
Section: Discussionsupporting
confidence: 81%
“…As mentioned above, most of the Aphanius species are similar in their external morphology, which has made them a difficult fish group to be identified for several years (Coad, 2000;Teimori et al, 2012a;Hrbek et al, 2006). Therefore, the objective of this study was to evaluate whether the urohyal bone morphology would be able to discriminate the selected Aphanius species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent studies have suggested that active geological history of the Zagros Mountains has considerably influenced diversification of the animals in the studied region especially reptiles and freshwater fishes (Rastegar-Pouyani and Nilson, 2002;Hrbek et al, 2006;Teimori et al, 2012). It is particularly true in the case of freshwater fishes because of their especial pattern of distribution, in which geologic divergence can act as a major physical barrier and produce several allopatric populations.…”
Section: Geologic History Fragmentation Of Populations and Biogeogramentioning
confidence: 99%
“…Iran is considered as a center for Aphanius diversity, with 14 species recognized and their distribution area include both freshwater and brackish water bodies (Teimori et al 2012;Gholami et al 2014a;Esmaeili et al 2014). Among 14 described Aphanius species in Iran, A. sophiae (Heckel, 1849) or soffia tooth-carp is endemic species restricted to the endorheic Kor River basin (Teimori et al 2012;Gholami et al 2014b).…”
Section: Introductionmentioning
confidence: 99%